Esophagus Tissue Engineering: Designing and Crafting the Components for the “Hybrid Construct” Approach - Saxena, Amulya K. (European Journal of Pediatric Surgery, 2014)
Although being a tubular structure, the esophagus is an extremely complex organ to engineer. To engineer an organ, its components and their structure and function must be well understood. With regards to esophagus, extensive investigations have been performed in experimental models to understand the nature of the esophageal epithelial cells with regards to their isolation, culture, and growth on scaffolds to generate epithelium. Special subpopulations of these cells have been identified that possess proliferative capabilities with subsequent differentiative capacity to generate epithelium. Studies have also been performed to obtain data on the possibilities of utilizing esophageal biopsies from esophagus damaged after caustic exposure for tissue engineering applications. Subsequently, attention is being paid to the esophageal smooth muscle which is an extremely complex structure responsible for the propulsive activities. In addition to the muscle complex, proper functioning of the esophagus will require understanding of the enteric nervous system (ENS) that controls the propulsive activity in a coordinated manner. Investigations have been performed to better understand the esophageal ENS and to isolate and maintain these cells under tissue culture conditions. Besides the cellular elements, studies have also been performed to seed these cells on scaffolds and study the constructs with regards to cell attachment and viability under tissue culture conditions. Tests have also been performed on native esophageal tissue to understand the functioning of this tissue under the effect of pharmacological agents and to establish norms to compare engineered esophageal tissue. Vascularization, which is a limiting factor in tissue engineering, has been approached with the in situ bioreactor concept using the omentum not only to provide vascular ingrowth but also to offer a pedicle for the engineered esophagus to enable its surgical transposition. This review offers an insight into the advances in esophagus tissue engineering in a large experimental model using the “hybrid construct” approach which advocates the precise engineering of the tubular gastrointestinal organs based on growth of specific cells on specially designed scaffolds and amalgamating them to create the desired complex tissue structure.
Keywords: tissue engineering; esophagus; scaffolds; bioreactors; epithelial cells; enteric nervous system; smooth muscle